A Prototype of IoT-Based Indoor Hydroponics Using MQTT for Sustainable Urban Housing - Andre Kurniawan Pamudji; Cindy Fiolita Graciela; Stephani Inggrit Swastini Dewi; Marcella Adelia Putri; Vincenzhea Chrissa Siwi; Nesia Rani Wijaya (SISFORMA, 2026)
Urban population growth significantly reduces the availability of open land for household farming, thus threatening urban food security. Indoor hydroponics offers a space-efficient solution, but manual maintenance often lags behind in addressing water quality fluctuations. Although IoT solutions have been widely developed, they generally still rely on rigid local servers or hardcoded Wi-Fi configurations, thus limiting multi-device scalability. This research aims to develop an indoor hydroponic automation and monitoring system using a hybrid communication architecture to support remote deployment without complex configuration. Adopting the Prototyping Software Development Life Cycle (SDLC) model, this research integrates Information Systems with green architecture. The hardware side is based on a WeMos D1 R32 microcontroller connected to an analog pH sensor, a water level sensor, and a 4-channel active-low relay module to control LED growlights and three mini submersible pumps in separate water and nutrient tanks. The HiveMQ Cloud Broker infrastructure was used to facilitate asynchronous telemetry over TCP port 1883 and data delivery to the browser via WebSockets port 8000 using the Eclipse Paho JavaScript library. Results: A physical prototype was successfully realized in the form of a compact vertical rack. The Trimmed Mean Filter algorithm in the firmware indicated reliable performance under the tested scenario in stabilizing the noise of analog pH readings. The web dashboard successfully processed JSON and updated the telemetry graph responsively during functional testing. The automatic extraction of the device's MAC Address successfully isolated MQTT topics to prevent data collisions between devices. Conclusion: This system effectively addresses the limitations of urban residential space through a biophilic design approach while providing an adaptive smart living solution for urban communities.